Transesophageal Echocardiography for Parachute-Like Asymmetrical Mitral Valve with Hypertrophy of the Left Ventricle and a Dominant Papillary Muscle in an Adult. (September 2016) - Kuroda, Masataka; Miyoshi, Sohtaro; Saito, Shigeru; Taguchi, Shingo
Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 9, 2016